A novel classification of the anatomical variations of the first extensor compartment. Issue 35 (September 2017) - Gao, Zheng-Yu; Tao, Hao; Xu, Hao; Xue, Jun-Qiang; Ou-Yang, Yao; Wu, Ji-Xia
Abstract : Abstract: The presence of a septum in the first extensor compartment is closely associated with the pathophysiology of de Quervain disease, and affects the efficacy of corticosteroid injection and surgical release. This study aimed to examine the incidence and length of the first extensor compartment septum. Forty sides of the wrists in 20 cadavers were used. The presence of a septum in the first extensor compartment was examined. The septum length was recorded with the radial styloid process as the reference point. The anatomical variations of the first extensor compartment were classified into 3 types. Type I compartment was found in 7 sides in males (29.2%) versus 6 sides in females (37.5%, P   =  .733), type II was found in 6 sides in males (25%) versus 1 side in females (6.25%, P  = .21), and type III was found in 11 sides in males (45.8%) versus 9 sides in females (56.25%, P  = .56). There was no significant difference in the septum length between males and females (5.3 ± 2.3 vs 4.8 ± 1.1 mm, P  = .54). The incidence of a septum in the first extensor compartment is approximately 50%. The mean septum length is 5 mm. Injection at 5 mm proximal to the radial styloid process has a great chance of delivering the steroids into both subcompartments. Exposure to 5 mm proximal to the radial styloid process can avoid the overlook of subcompartment and achieve adequate decompression of the first extensor compartment.